An inquiry into the nature and causes of the Description - Experience gap - Robin P. Cubitt; Orestis Kopsacheilis; Chris Starmer (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2020)
The Description-Experience gap (DE gap) is widely thought of as a tendency for people to act as if overweighting rare events when information about those events is derived from descriptions but as if underweighting rare events when they experience them through a sampling process. While there is now clear evidence that some form of DE gap exists, its causes, exact nature and implications for economic theory remain unclear, for reasons we explain. We present a new experiment which examines in a unified design four distinct causal mechanisms that might drive the DE gap, attributing it respectively to information differences (sampling bias), to a feature of preferences (ambiguity sensitivity) or to aspects of cognition (likelihood representation and memory). Using a model-free approach, we elicit a DE gap similar in direction and size to the literature's average and find that, when each factor is considered in isolation, sampling bias stemming from under-represented rare events is the only significant driver of the gap. Yet, model-mediated analysis reveals the possibility of a smaller DE gap, existing even without information differences. Moreover, this form of analysis of our data indicates that, even when information about them is obtained by sampling, rare events are generally overweighted.
Keywords: D81; C91; D91; 330; Decisions from Description; Decisions from Experience; Risk Preferences; Cumulative ProspectTheory; Ambiguity